Advancing Construction Scheduling: Unravelling Challenges Through GERT - Pregina, K.; Vasugi, K. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Many real-time projects face uncertainty and unpredictability in today’s rapidly developing world, rendering conventional scheduling methods inadequate. In such circumstances, stochastic scheduling emerges as a valuable mechanism for formulating dependable and efficient schedules while simultaneously considering the intrinsic uncertainty and variability of the factors that impact the project. Graphical Evaluation and Review Technique (GERT) is a stochastic method employed in project management to model and analyses complex projects. The article provides an in-depth examination of GERT methodology literature, addressing its historical background, fundamental principles, methodologies, limitations, and practical applications. This comprehensive analysis involves informetric evaluation and content classification, encompassing a total of 96 journal articles, 10 book chapters, and 39 conference papers published from 1997 to 2023. It furnishes valuable insights to aid researchers and decision-makers in making informed decisions and enhancing the efficiency of project planning, scheduling, and control.